MATHEMATICAL UNDERSTANDING AND REPRESENTATION ABILITY OF PUBLIC JUNIOR HIGH SCHOOL IN NORTH SUMATRA - Minarni, Ani; Napitupulu, Elvis; Husein, Rahmad (Journal on Mathematics Education, 2016)
This paper is the result of first phase of the research about the development of students’ mathematical understanding and representation ability through Joyful Problem-based Learning (JPBL) at Public Junior High School in North Sumatera, Indonesia. The population is all of the students of public junior high school (PJHS) in North Sumatera. Samples choose based on stratified random sampling. The samples are the students of PJHS 27 Medan, PJHS 1 Percut Sei Tuan, PJHS 1 Tebing Tinggi, and PJHS 2 Pematangsiantar. The techniques used for collecting data is observation, interview, and essay test. The research findings: (1) Based on interview and observation found that conventional approach still use in all of the class of PJHS; The students engagement in learning activity is very low as well as students self-regulated learning; Most of the students do not attain minimal mastery achievement, (2) Based on essay test found that achievement of the students in mathematical understanding and representation test is categories low.Keywords: mathematical understanding, mathematical representation, joyful problem-based learning DOI: http://dx.doi.org/10.22342/jme.7.1.2816.43-56